Evaluating ICT Integration and Gender Equality in Physics Education among Ugandan Teacher Trainees - Waninga, Willy; Olinga , John Paul; Opus , Michael; Ajuko , Annah Grace (Journal of Education and Practice, 2025)
Purpose: This study assessed the ICT competences of student teachers and their application in physics education. It aimed to explore their preparedness to utilize ICT in teaching and learning physics, focusing on gender disparities and systemic inequalities in access to resources and training. The study was framed within the Technological Pedagogical Content Knowledge (TPACK) model, Diffusion of Innovations (DOI), and sociocultural theories. Methodology: The study employed a qualitative approach using survey and case study designs. Data were collected through surveys, document analysis, observations, and interviews with science student teachers enrolled in a Diploma in Education program. Content and thematic analysis was used to analyze the data, providing a comprehensive understanding of the participants’ ICT competences and their applications in physics education. Findings: The findings revealed that student teachers possess foundational ICT skills, including integrating technology into lesson planning and conducting online research. However, gender disparities in competence levels and systemic barriers, such as unequal access to training and technological infrastructure, were evident. These factors hindered equitable ICT integration in physics education and limited the effective utilization of technology for teaching and learning. Unique Contribution to Theory, Practice, and Policy: The study emphasized the need for targeted curriculum reforms to integrate ICT effectively and address gender disparities. It highlighted the importance of professional development initiatives to equip educators with advanced ICT skills and foster digital literacy. The findings provide valuable insights for policymakers to develop strategies aimed at reducing systemic inequalities and ensuring inclusive, technology-enhanced learning environments in physics education.